SHIFTING SPECTACLE OF THYROID ANTIBODIES: A UNIQUE PRESENTATION - Aziz, Abd Jalil bin Abd; Jalal, Fadzliana Hanum (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Graves’ disease typically manifests with hyperthyroidism. However, the switch between TSH receptor-stimulating antibodies (TSAb) and TSH receptor-blocking antibodies (TSB Ab) is uncommon. We discuss three patients with Graves’ disease who switched between hypothyroidism and hyperthyroidism throughout the course of their disease. CASE Case A involves a 44-year-old female with initial diagnosis of hyperthyroidism. She was treated with carbimazole for two years and remained euthyroid for a few years without medication. Four years following the diagnosis, she developed overt hypothyroidism requiring levothyroxine. She remained hypothyroid for nine years until her TSH levels trended towards the lower end, hence, she was restarted on carbimazole. She had elevated TRAb [2.0 IU/L, N: <1.75] and anti-TPO [890 IU/ml, N:<9] at screening. Her neck ultrasound showed a goitre with a solitary left thyroid nodule. Case B involves a 68-year-old male diagnosed with hyperthyroidism [FT4: 140 pmol/L, TSH:0.008 m IU/L]. Twelve months following diagnosis, he developed overt hypothyroidism while on low dose carbimazole and eventually required levothyroxine. Thyroid antibodies were elevated [TRAb 37 IU/L and anti-TPO 534 IU/ml]. His neck ultrasound revealed a small thyroid nodule with benign features. Case C is a 43-year-old female who presented with overt hypothyroidism [Ft4 9 pmol/L,TSH 95.75 m IU/L] and was treated with levothyroxine. Initial antibodies were elevated [anti-TPO 235 IU/ml, anti-Tg 104.8 IU/ml]. Three years following diagnosis, her TSH levels trended towards the lower ranges and eventually showed overt hyperthyroidism [FT4 28, TSH <0.008]. She was commenced on oral carbimazole. Repeat antibodies were elevated [antiTg 30 IU/ml, anti-TPO 218.25 IU/ml, TRAb 23.8 IU/L]. Her neck ultrasound showed multiple subcentimetre thyroid nodules. CONCLUSION Graves’ disease is characterized by the presence of TRAb, which can exhibit either TSAb or TSB Ab activity. Treatment with anti-thyroid drugs (ATD) such as carbimazole may further trigger the switch to hypothyroidism. Therefore, close monitoring and follow-up are crucial for these patients.